(untitled) (Paris, 1960)
These methods should avoid lengthy computations and should render results that can be easily verified. This handbook endeavours to summarize some of the rational graphical methods, based on simple hypotheses generally accepted today.
Keywords: Building engineering,Kỹ thuật xây dựng